An examination of factors that may contribute to gender differences in psychomotor processing speed - Eka Roivainen (BMC, 2021)
Abstract Background For unknown reasons, females outperform males on tests of psychomotor processing speed (PS), such as the Coding and Symbol Search subtests of the Wechsler Adult Intelligence Scale. Method In the present study, the effects of intelligence, memory, personality, fine motor speed, gross motor dexterity, height, weight, age, sex, and education on psychomotor processing speed were studied in an outpatient sample (n = 130). Results Moderate (r > .40) correlations were found between PS and verbal reasoning, nonverbal reasoning, verbal memory, and fine motor speed. Weak (r > .20) correlations were found between PS and gross motor dexterity, extraversion, education, weight, and sex. Females outperformed males in PS and in fine motor speed. Stepwise linear regression analysis indicated nonverbal reasoning, fine motor speed, and sex as independent predictors of PS. Conclusions One interpretation of the results is that the factors underlying sex differences in processing speed are not psychological but neurological or physiological in nature and therefore a wider variety of measures from these disciplines are needed for further studies. For clinical assessment purposes, psychological tests should preferably provide different norms for male and female PS scores.